Penggunaan model cooperative script untuk meningkatkan keterampilan membaca pemahaman pada siswa kelas V di sekolah dasar - Dina Ramadhanti; Rukayah Rukayah; Tri Budiharto (Universitas Sebelas Maret, 2021)
This research servers as an effort to improve student’s reading comprehension skills through the application of the Cooperative Script model for student 5th grade of elementary school student at Surakarta on 2019/2020 school year. The subject of this study were 19 students from 5th grade of elementary school and class teacher. This research is a classroom action implementation, observation, and reflection. Data collection methods used are observation, test, interview, and document analysist. This study uses descriptive data analysist with a qualitative approach that describe data obtained by researchers from the result of the implementation of the action. This study found success in increasing the average value from cycle I to cycle II, the average value of cycle I was 71,73 with classical completeness 36,84%, increasing in cycle II that was 85,18 with classical completeness 89,47%. The output of this study indicated that by applying the Cooperative Script learning model can improve student’ reading comprehension skill, student activity, and teacher performance